1999
DOI: 10.1046/j.1365-2273.1999.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postoperative facial nerve function in acoustic neuroma surgery

Abstract: There is a need for an uncomplicated, consistent method to predict facial nerve function after acoustic neuroma surgery. A prospective study with a 2-year follow-up of 35 patients undergoing acoustic neuroma surgery was performed assessing how well intraoperative facial nerve monitor electrophysiological thresholds and facial function postsurgery can predict ultimate nerve function. Tumour size was a strong predictor of immediate (P-value < 0.0005) and long-term facial nerve function (P-value = 0.004). Immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…Although tumor size alone should not be considered as a predictive factor, it has been thought to be the most important one 9,10 . Gormley 28 showed that 96% of patients with small tumors had postoperatively normal facial function or slight dysfunction (Grade I-II), whereas only 38% of patients with tumors greater than 4.0 cm had no dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tumor size alone should not be considered as a predictive factor, it has been thought to be the most important one 9,10 . Gormley 28 showed that 96% of patients with small tumors had postoperatively normal facial function or slight dysfunction (Grade I-II), whereas only 38% of patients with tumors greater than 4.0 cm had no dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that tumor size is an approximate guide to predicting ultimate functional outcome 9,10 . The objective of this study is to analyze the facial nerve function in patients submitted to VS surgery by the retrosigmoid transmeatal approach and correlate tumor size with the grade of postoperative facial palsy (FP).…”
Section: Dra Rafaela Júlia Batista Veronezi -Rua Santaré� Qd 235 Lt mentioning
confidence: 99%
“…14) Tumor size is the most important predictor of facial nerve palsy. 6) Other predictors of facial nerve function are displacement of the fourth ventricle, image heterogeneity (necrosis, edema, cystic change), and the threshold stimulus eliciting a facial nerve response. 4) H. J. Seol et al…”
Section: Facial Nerve Preservationmentioning
confidence: 99%
“…27 In the present study, we investigated a method of hypoglossal-facial nerve anastomosis through an NT3-expressing PNG engineered by lentiviral vectors to treat complete facial palsy in adult rats. Since surgical treatment for facial palsy in humans is usually performed with a delay between trauma and repair, 9,36 facial nerve reconstruction in our study was performed either immediately after facial nerve injury or 9 weeks posttrauma. After a minimum of 4 months of postsurgical recovery, the outcomes of different treatments were assessed in the animals via functional, electrophysiological, and histological examinations.…”
mentioning
confidence: 99%